Evaluation of cytokines and soluble adhesion molecules in patients with newly diagnosed acute myeloid leukemia: the role of TNF-alpha and FLT3-ITD - Tomas Kupsa; Jan Vanek; Martina Vasatova; Iva Karesova; Pavel Zak; Ladislav Jebavy; Jan M. Horacek (Biomedical Papers, 2016)
Objectives: Acute myeloid leukemia (AML) cells are highly resistant to therapy. The presumed molecular basis of this resistance is the effect of tumor necrosis factor alpha (TNF-α) and other cytokines on endothelial adhesion molecule expression. The aim of this study was to test the hypothesis that cytokines and soluble adhesion molecules correlate in AML. Methods: Baseline serum levels of 17 cytokines and 5 soluble adhesion molecules were measured in 53 AML patients using biochip array technology. Age, leukocyte count, secondary AML, CRP, FLT3-ITD and remission were variables. Statistical analysis was performed in R version 3.1.2. Results: VCAM-1 correlated with ICAM-1 (P < 0.0001), E-selectin (P < 0.0001), leukocyte count (P = 0.0005) and TNF-α (P = 0.0035). E-selectin correlated with leukocyte count (P < 0.0001), P-selectin (P = 0.0032) and MCP-1 (P = 0.0119). CRP correlated with IL-6 (P < 0.0001), leukocyte count negatively correlated with IL-7 (P = 0.0318). FLT3-ITD was associated with higher E-selectin (P = 0.0010) and lower IL-7 (P = 0.0252). Secondary AML patients were older. Failure of induction therapy was associated with significantly higher CRP and lower P-selectin. Leukocyte count (P < 0.0001), FLT3-ITD (P = 0.0017) and secondary AML (P = 0.0439) influenced the principal component. Conclusions: Leukemic cells can modulate the microenvironment. Cytokine, adhesion molecule levels and leukocyte count correlate in AML. Understanding these mechanisms may form the basis of novel therapeutic approaches.